2020
DOI: 10.1186/s12610-020-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of relaxin for cisplatin-induced testicular dysfunction and epididymal spermatotoxicity

Abstract: Background: Cisplatin (CP) is an extremely effective anticancer agent widely used to treat various cancer types, however, the potential side effects include testicular dysfunction. This study was to investigate, using a rat model of CP-induced testicular dysfunction, the protective effects of relaxin (RLN) against oxidative stress, testicular function, histological damage, spermatogenesis, germ-cell apoptosis, and sperm output, and to explore the usefulness of RLN as a potential protective drug for use with CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…When gonadotropin luteinizing hormone is released, it results in cAMP release and protein kinase A activation, which initiates a series of enzyme cascade reactions (Liu et al, 2015). In various studies examining the effects of CP on testicular and reproductive function, it has been shown that plasma or testicular total and free testosterone levels are also reduced; these results have often been associated with oxidative stress (Azab et al, 2020;Ceylan et al, 2020;Famurewa et al, 2020;Jourabi et al, 2020;Kohsaka et al, 2020;Majd et al, 2021;Saad et al, 2020;. In the present study, we also demonstrated that CPinduced oxidative stress significantly decreased total and free testosterone levels in rats' plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When gonadotropin luteinizing hormone is released, it results in cAMP release and protein kinase A activation, which initiates a series of enzyme cascade reactions (Liu et al, 2015). In various studies examining the effects of CP on testicular and reproductive function, it has been shown that plasma or testicular total and free testosterone levels are also reduced; these results have often been associated with oxidative stress (Azab et al, 2020;Ceylan et al, 2020;Famurewa et al, 2020;Jourabi et al, 2020;Kohsaka et al, 2020;Majd et al, 2021;Saad et al, 2020;. In the present study, we also demonstrated that CPinduced oxidative stress significantly decreased total and free testosterone levels in rats' plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that Pnx might promote the testosterone secretion of Leydig cells via suppressing oxidative stress which was induced by CP in rat testes. Kohsaka et al reported that CP causes an increase in TUNEL (+) spermatogenic and Leydig cells apoptotic index; however, it reduces Johnsen's score in rats' testes (Kohsaka et al, 2020). Research on the protective effect of caffeic acid phenethyl ester on testicular damage caused by CP showed that CP decreased Johnsen's score and damaged spermatogenic cells (Ceylan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is the most commonly known chemotherapeutic among chemotherapy drugs (Dasari & Tchounwou, 2014;Hanif & Hartinger, 2018). Although CP is used in many cancer treatments, it has many side effects including neurotoxicity, nephrotoxicity, hepatotoxicity, gonadotoxicity (Lu et al, 2006;Santos et al, 2008;Melli et al, 2008;Quintanilha et al, 2017;Kohsaka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But the sperm quality analysis of TP and YP raised at high altitudes have not yet been conduced. Proteomic data enable a better understanding of sperm biochemistry [5]. In-depth proteomic analysis of boar spermatozoa was implemented using shotgun and gel-based methods [6].…”
Section: Introductionmentioning
confidence: 99%